Effect of calcination time on the electrochemical performance of LiNi0.8Co0.1Mn0.1O2 cathode materials. Issue 5 (April 2020) - Bai, Xue; He, Rui; Zhang, Lihui; Liu, Zhenfa
Abstract: The layered Ni-rich LiNi0.8 Co0.1 Mn0.1 O2 cathode materials were synthesized by a solid-state method at different calcination times. The structure, morphological and electrochemical performance of the synthesized materials were studied by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and galvanostatic charge-discharge tests. The results indicate that the sample prepared at 20h delivers higher rate capacities of 184.8, 182.8, 171.2, 158.3, 142.8, and 116.4 mAh g −1 at rates of 0.1C 0.2C, 0.5C, 1C, 2C, and 5C, respectively. And the sample prepared at 16h exhibits better cycle stability than others.